A systematic study on requirement engineering processes and practices in Mauritius - Huzoree, Geshwaree; Ramdoo, D. (Advanced Research International Publication House, 2015)
Requirement engineering processes have been used for many years in software development. The processes consist of four stages namely elicitation, analysis and negotiation, specification, and validation. The appropriate use of the different stages for a given project, and tailoring the stages to a specific requirement has been a challenge since requirement engineering varies from organization to organization. Nowadays, more than ever, software development projects are geared towards failures due to poor requirements. This paper analyses the requirement engineering processes across different organizations with the aim of identifying the difficulties that are encountered in the requirement engineering processes and the gap that exists between theory and practice. As resolution, solutions have been proposed to overcome the difficulties encountered and to bridge the gaps resulting in enhanced requirement engineering and potentially much better software.